2022
DOI: 10.1021/acs.jpca.1c06115
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Ab Initio Optical Absorption Spectrum of β-Carotene with Fully Resolved S0 and S2 Vibrational Normal Modes

Abstract: The electronic absorption spectrum of β-carotene (β-Car) is studied using quantum chemistry and quantum dynamics simulations. Vibrational normal modes were computed in optimized geometries of the electronic ground state S 0 and the optically bright excited S 2 state using the time-dependent density functional theory. By expressing the S 2-state normal modes in terms of the ground-state modes, we find that no one-to-one correspondence between the ground- and excited-state vibrational modes exists. Using the ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 73 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…It is therefore interesting to look at the vibrational mode wavepacket transition from being represented by the D 2 to a more complex mD 2 Ansatz. This transition occurs naturally in eqn (10), for the computation of the linear response function, when an upward transition dipole operator acts on the aggregate ground state, as given by eqn (11). One way to track wavepacket changes is to consider its coordinate and momentum variances, given by…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore interesting to look at the vibrational mode wavepacket transition from being represented by the D 2 to a more complex mD 2 Ansatz. This transition occurs naturally in eqn (10), for the computation of the linear response function, when an upward transition dipole operator acts on the aggregate ground state, as given by eqn (11). One way to track wavepacket changes is to consider its coordinate and momentum variances, given by…”
Section: Discussionmentioning
confidence: 99%
“…After independently propagating bra (L) and ket (R) states of eqn (10), their overlap is given by S ð1Þ ðtÞ ¼ C…”
Section: Theory and Its Numerical Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been extensively used to compute spectra of molecules as well as to examine excitation relaxation dynamics in single molecules and their molecular aggregates. [7][8][9][10][11][12][13][14] The trial wavefunction's selection greatly influences how accurate the method is. It has been shown that in some cases for precise modeling of molecular aggregates, the D 2 ansatz falls short, 15 however, the accuracy of vibrational mode representation can be improved by expanding the available parameter space.…”
Section: Introductionmentioning
confidence: 99%